Implementasi Pembelajaran Pendidikan Agama Islam Berbasis Learning Management System Moodle di SMP Al-Fath Cirendeu - Hunafa Ulfitriyah; Yayah Nurmaliah; Heny Narendrany (Syntax Corporation Indonesia, 2024)
The purpose of this study is to describe learning based learning management system in SMP Al-Fath Cirendeu. This study used a descriptive qualitative approach. Data collection is carried out by; observation, interviews, and documentation. Technical data analysis by reducing data, display data and verification. From this study, it was obtained that LMS learning planning at SMP Al-Fath Cirendeu in its stages has a point of difference with learning planning in general, where there are stages for uploading material, converting material and publishing material before the material is taught in class. In its implementation, SMP Al-Fath Cirendeu utilizes LMS as a medium to deliver material, conduct discussions and collect various tasks in the LMS. Learning model with blended learning, learning approach using discovery learning, the method generally uses discussion and presentation. As for the evaluation stage, teachers use quizzes and assignments at the end of each lesson that will be uploaded in the LMS.